The Influence of Mode-of-Injury on Psychological Readiness for Return-To-Sport Following Anterior Cruciate Ligament Reconstruction: A Matched-Controlled Study - Jenifer Presley (North American Sports Medicine Institute, 2021)
# Background Self-efficacy and fear of re-injury have been documented as factors related to an athlete’s ability to return-to-sport after anterior cruciate ligament (ACL) reconstruction. The purpose of this study was to compare psychological readiness between athletes injured in their primary mode of sport versus those injured outside of their primary sport following ACL reconstruction.